Influence of Sulfuric Acid on the Tensile Properties of Halloysite Reinforced Polyurethane Composite / Tayser Sumer Gaaz...[et al.] - Tayser, Sumer Gaaz; Sulong, Abu Bakar; H. Kadhum, Abdul Amir (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In this study, the mechanical properties of injection molded of HNTs-TPU composites were investigated. The composites were first made by adding halloysite nanotubes (HNTs) at weight percentages of 1, 2, and 3 wt.% to thermoplastic polyurethane (TPU). Then, HNTs were sulfuric acid-treated before adding to TPU at same weight percentage to create sulfuric acid HNTs-TPU composites. The samples were fabricated using injection molding. The HNTs-TPU composites were characterized according to the mechanical properties, including tensile strength, tensile strain and Young’s modulus. The highest mechanical values obtained at 2 wt.% HNTs loading, and similar findings are shown at the samples treated with sulfuric acid. The tensile strength increased until reach 23.78 MPa compare with the 17.7 MPa of the neat TPU, which showing about 25% improvement. For the acid-treated composites, the improvement has reached 34.4% compared to the neat sample. Regarding the tensile stain, the improvement was about 82% at 2 wt.% HNTs loading. The Young’s modulus results obtained in this study have shown that it is linearly improved with increment of loading content and sulfuric acid treated of HNTs. Where it achieving the highest values of Young’s modulus at 3 wt.% HNTs of 13.3 MPa and 15.2 MPa for untreated and treated, respectively.